Identification and in vivo evaluation of a fluorine‐18 rolipram analogue, [18F]MNI‐617, as a radioligand for PDE4 imaging in mammalian brain. (22nd March 2016) - Thomae, David; Morley, Thomas J.; Lee, Hsiaoju S.; Barret, Olivier; Constantinescu, Cristian; Papin, Caroline; Baldwin, Ronald M.; Tamagnan, Gilles D.; Alagille, David
Abstract : Phosphodiesterase (PDE) 4 is the most prevalent PDE in the central nervous system (CNS) and catalyzes hydrolysis of intracellular cAMP, a secondary messenger. By therapeutic inhibition of PDE4, intracellular cAMP levels can be stabilized, and the symptoms of psychiatric and neurodegenerative disorders including depression, memory loss and Parkinson's disease can be ameliorated. Radiotracers targeting PDE4 can be used to study PDE4 density and function, and evaluate new PDE4 therapeutics, in vivo in a non‐invasive way, as has been shown using the carbon‐11 labeled PDE4 inhibitor R ‐(−)‐rolipram. Herein we describe a small series of rolipram analogs that contain fluoro‐ or iodo‐substituents that could be used as fluorine‐18 PET or iodine‐123 SPECT PDE4 radiotracers. This series was evaluated with an in vitro binding assay and a 4‐(fluoromethyl) derivative of rolipram, MNI‐617, was identified, with a five‐fold increase in affinity for PDE4 ( K d  = 0.26 nM) over R ‐(−)‐rolipram ( K d  = 1.6 nM). A deutero‐analogue d2 ‐[ 18 F]MNI‐617 was radiolabeled and produced in 23% yield with high (>5 Ci/µmol) specific activity and evaluated in non‐human primate, where it rapidly entered the brain, with SUVs between 4 and 5, and with a distribution pattern consistent with that of PDE4. Abstract : Phosphodiesterase (PDE) 4 is the most prevalent PDE in the central nervous system and catalyzes hydrolysis of intracellular cAMP, a secondary messenger. Herein, we describe a small series of rolipram analogs that contain fluoro‐ or iodo‐substituents that could be used as fluorine‐18 PET or iodine‐123 SPECT PDE4 radiotracers. This series was evaluated with an in vitro binding assay, and a 4‐(fluoromethyl) derivative of rolipram, MNI‐617, was identified, with a fivefold increase in affinity for PDE4 (Kd = 0.26 nM) over R‐(‐)‐rolipram (Kd = 1.6 nM).